Daya Hasil Galur-Galur Elit Padi di Lahan Sawah Rawan Salin di Cilamaya Wetan Karawang - Nafisah Nafisah; Aris Hairmansis; Trias Sitaresmi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Nafisah et al, 2017. Grain Yield of Rice Elite Lines Under Saline Prone Condition in Cilamaya Wetan, Karawang Subdistrict West Java. JLSO 6(1):21-32.Utilization of high yielding rice varieties tolerant to salinity is one way to maintain yield sustainability in salt affected rice area. As many as 30 elit lines and 4 varieties checks were tested in saline prone area in Muara Baru, Cilamaya Wetan sub district, Karawang, West Java. The trial was arranged in Randomized Block Design with three replications. Twenty eight old seedlings were planted in 3x4 m2 plot size with 25 cm x 25 cm planting space. Analysis variance showed two elit lines (1131-Ski-4 dan IR86385-50-2-1-B-SKI-2) yielded 5.48 dan 5.64 t/ha, respectively. These yield were significant higher than those of two popular checks planted by local farmers, i.e.  Mekongga and Sintanur which yielded about 4,44 t/ha. Beside 11 lines  had yield 0,5 t/ha higher than that of popular check variety.  Correlation analysis showed grain yield highly positive correlated with productive tiller number and filled grain number, while thousand grain weight highly positive correlated with plant height. Screening for salinity tolerance in seedling stage done in screen house showed that both 1131-Ski-4 dan BP14082-2b-2-5-TRT-35-2-SKI-1 consistently tolerant under salinized Yoshida solution at 12 dSm-1. These two lines are very potential for further tested in saline prone area.